Introduction of dual training in Slovakia : Initial steps towards closer cooperation between schools and companies - Geiben, Marthe [Verfasser]; Csépe-Bannert, Eszter [Verfasser] (My University, 2018)
"In 2015, Slovakia passed a new vocational education and training act which also encompasses the introduction of dual training. Its provisions also include stipulations governing new opportunities for cooperation between the state and trade and industry at a national level and between schools and business both regionally and locally. This article presents these regulations and describes initial experiences with implementation by taking the development of training programmes for shoe makers as an example." (authors' abstract; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; I 2.2.2 Osteuropa; Berufsbildungsrecht; Berufsbildungssystem; Duales System; Kooperation Schule Wirtschaft; Schumacher; Slowakei